COMPARATIVE ANALYSIS OF PHYSICAL-CHEMICAL PARAMETERS OF DOMESTIC TRITICALE GRAIN - RAVSHANOV, SUVONKUL; MIRZAEV, JAMOL; ADULLAYEV, SIROJIDDIN; OBIDOV, JAVOKHIRBEK (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article carried out a comparative analysis of the physicochemical parameters of triticale grains in comparison with grains of wheat and rye. To analyze the physicochemical parameters of grain samples, the standards GOST 13586.5-85, 10840-64, 10842-89, 10987-76, 10847-74, 23586.1-68 were used. The purpose of the research is to compare the physicochemical parameters of local triticale grain and study its technological capabilities for obtaining flour.